The Puntano rain gauge: A robust solution for rainfall data collection in harsh field conditions - Magliano, Patricio Nicolás (2026)
Rainfall data is essential for conducting most field-based environmental studies. While the number of rainfall measurement stations and satellite estimations has increased substantially in recent decades, generating accurate time series remains a major challenge in arid, remote, or hard-to-access regions. Conventional rain gauges require either daily manual readings or frequent maintenance in the case of electronic devices. In this paper, we present the “Puntano rain gauge,” a robust and maintenance-free device designed to reliably measure rainfall under extreme environmental conditions. Depending on the site characteristics, Puntano can record continuous rainfall data for up to 2 years at hourly resolution. This performance is achieved through a water level difference method using pressure transducers, rather than conventional tipping bucket or drop-counting mechanisms. Puntano was validated against standard stations under real field conditions, demonstrating high accuracy at the event scale (R2 = 0.98, p < 0.01), daily scale (R2 = 0.92, p < 0.01), and hourly scale (R2 = 0.82, p < 0.01). These results support Puntano as a suitable solution for rainfall monitoring in remote locations, harsh environments, and areas without internet connectivity.